1995
DOI: 10.1152/ajplung.1995.268.2.l230
|View full text |Cite
|
Sign up to set email alerts
|

Insulin modulation of bronchial epithelial cell fibronectin in vitro

Abstract: Fibronectin (Fn) is involved in the migration of epithelial cells in re-epithelialization of wounds. Epithelial cell-derived Fn is particularly potent as a chemotactic factor for bronchial epithelial cells (BECs) in vitro. Thus modulation of airway epithelial cell Fn may be a key aspect of airway repair. Insulin is both an important growth factor and known chemotactic factor for cultured BECs. We postulated that insulin may modulate Fn production of cultured BECs. We examined this hypothesis utilizing bovine B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a similar study, Rickard and associates (22) demonstrated that both freshly isolated and cultured bovine bronchial epithelial cells adhered equally well to fibronectin, laminin, and collagen IV. Epithelial cells make fibronectin in response to inflammatory mediators (23,24), and it has been suggested that both fibronec- Figure 5. Closure of monolayer wounds in GPTEC monolayers after treatment with EGF.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, Rickard and associates (22) demonstrated that both freshly isolated and cultured bovine bronchial epithelial cells adhered equally well to fibronectin, laminin, and collagen IV. Epithelial cells make fibronectin in response to inflammatory mediators (23,24), and it has been suggested that both fibronec- Figure 5. Closure of monolayer wounds in GPTEC monolayers after treatment with EGF.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin Promotes the survival of epithelial cells 11 Participates in epithelium restoration integrity after its damage 12 Stimulates NO release from epithelial cells 13 Relaxes precontracted airways 13 Respiratory system is considered an alternative route for insulin administration for the treatment of type 1 diabetes mellitus 71 Low incidence of asthma in patients with diabetes mellitus 72…”
Section: Endogenous Factorsmentioning
confidence: 99%